Optical solitons in passively mode-locked fiber ring lasers - Zhao, Bin (2008)
Optical solitons have attracted especial attention due to their theoretical importance and potential practical applications in optical communications. Self-starting, passively mode-locked erbium-doped fiber lasers are promising sources of optical solitons for laboratory, telecommunication and signal-processing applications because of their simplicity, tunability and ultrashort pulse operation. Although this type of lasers have been intensively studied, many mechanisms are still not very clear. In this dissertation, the author presents a series of theoretical and experimental investigations on the soliton property, evolution, and interaction in a passively mode-locked erbium-doped fiber laser.